Skin lesions simulating child abuse - Sahana M Srinivas; Celia Moss (Wolters Kluwer Medknow Publications, 2018)
Child abuse is a broad term which describes various forms of maltreatment and neglect in children and is recognized increasingly. Physical abuse presents to dermatologists as well as pediatricians because the skin is so readily accessible for harm. Doctors unfamiliar with the wide range of skin disorders that simulate child abuse may mistakenly diagnose child abuse or "fabricated or induced illness by carers" (Munchausen by proxy), with traumatic consequences for the family. Mimics of child abuse include various cultural practices, birthmarks, bleeding disorders, bacterial infections, bullous diseases, and hereditary conditions. Dermatitis artefacta and self-harm must also be considered. Observation of the skin lesions and their evolution during hospitalization may provide the correct answer, but knowledge of the morphology and presentation of various skin disorders is crucial to avoid incorrect diagnosis of child abuse. This article describes some of the less well-known mimics of child abuse. It is essential that dermatologists support pediatricians in managing conditions that appear unusual and possibly artifactual.